PSMA radioligand uptake correlates with PSMA expression in high-grade glioma and brain metastasis: insights from a prospective PET-MRI guided multiregional biopsy study. - Pruis, Ilanah J.; van Dis, Vera; Maas, Sybren L. N.; Balvers, Rutger K.; van den Bosch, Thierry P. P.; Segbers, Marcel; Veldhuijzen van Zanten, Sophie E. M. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: Prostate-specific membrane antigen (PSMA) is a potential target for radioligand therapy (RLT) in neuro-oncology. This study investigates the direct relation between [68Ga]Ga-PSMA-11 uptake on PET and PSMA expression in the tumour micro-environment of high-grade glioma (HGG) and brain metastasis (BM). Methods: Twelve patients with HGG (glioblastoma n = 6, oligodendroglioma n = 1), or BM (lung- n = 4, breast cancer n = 1), underwent PET-MRI after intravenous [68Ga]Ga-PSMA-11 injection (1.5 MBq/kg), followed by image-guided biopsy sampling during (re-)resection surgery. Multiple samples (median n = 3/patient, n = 23 HGG/n = 20 BM) from locations of low and high [68Ga]Ga-PSMA-11 uptake were analysed for PSMA expression in vasculature and non-vascular structures using morphology and immunohistochemistry. Results: All patients showed [68Ga]Ga-PSMA-11 uptake in tumour (SUVmax median, range: 10.5, 4.7–19.8). Strong PSMA expression was found in tumour microvasculature (14/23, 61% in HGG, 13/20, 65% in BM). Tumour cell PSMA expression was found in a subset of HGG (10/23; of which strong in 8/10) and BM (3/20; none of which showed strong expression). Strong PSMA expression was also found on non-malignant glial cells in tumour. PSMA expression in healthy brain control samples was negligible. In HGG, a significant correlation existed between [68Ga]Ga-PSMA-11 uptake and PSMA expression in tumour microvasculature (r = 0.487, P < 0.01), but not tumour cells. Conclusion: PSMA expression in brain tumours is predominately vascular, which likely explains why microvascular (rather than tumour cell) PSMA expression correlates with [68Ga]Ga-PSMA-11 uptake in HGG. This neovascular expression is crucial information for future PSMA-based RLT studies, as alpha-emitters may not sufficiently target tumour DNA. NCT05798273; date of registration: 1/9/2020.